2020
DOI: 10.3390/ijerph17207600
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sleep Quality, Trait Anxiety and Hypothalamic-Pituitary-Adrenal Axis Measures in Cognitive Abilities of Healthy Individuals

Abstract: Sleep plays a crucial role in cognitive processes. Sleep and wake memory consolidation seem to be regulated by glucocorticoids, pointing out the potential role of the hypothalamic-pituitary-adrenal (HPA) axis in the relationship between sleep quality and cognitive abilities. Trait anxiety is another factor that is likely to moderate the relationship between sleep and cognition, because poorer sleep quality and subtle HPA axis abnormalities have been reported in people with high trait anxiety. The current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 86 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…The HPA axis also influences sleep: HPA activation leads to disturbed and lighter sleep, and inadequate sleep increases the HPA axis's basal activity [ 4 ]. Indeed, factors such as subtle HPA axis abnormalities and higher trait anxiety are associated with lower sleep quality and poorer cognitive functioning among healthy adults [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HPA axis also influences sleep: HPA activation leads to disturbed and lighter sleep, and inadequate sleep increases the HPA axis's basal activity [ 4 ]. Indeed, factors such as subtle HPA axis abnormalities and higher trait anxiety are associated with lower sleep quality and poorer cognitive functioning among healthy adults [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is further supported by recent studies showing that trait anxiety was associated with depression and poor sleep quality. [ 32 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…Labad et al looked at the relationship between sleep quality, cognitive functioning, and trait anxiety. They focused on adults who had no history of mental illness but scored low on the General Health Questionnaire-28 (GHQ-28), a self-report questionnaire that assesses symptoms of anxiety, depression, and insomnia [6]. Using a Neuropsychological Assessment Battery (NAB), they found that poor sleep quality was associated with poorer performance in verbal and visual memory, processing speed, and executive functioning [6].…”
Section: Trait Anxietymentioning
confidence: 99%
“…They focused on adults who had no history of mental illness but scored low on the General Health Questionnaire-28 (GHQ-28), a self-report questionnaire that assesses symptoms of anxiety, depression, and insomnia [6]. Using a Neuropsychological Assessment Battery (NAB), they found that poor sleep quality was associated with poorer performance in verbal and visual memory, processing speed, and executive functioning [6]. They also performed a saliva cortisol test to determine whether the Hypothalamic-Pituitary-Adrenal (HPA) axis activity had an effect on sleep quality and found that abnormalities in the HPA axis may cause an increase in cortisol that contribute to poorer processing speed [6].…”
Section: Trait Anxietymentioning
confidence: 99%
See 1 more Smart Citation